Nanocrystallinity and direct cross-linkage as key-factors for the assembly of gold nanoparticle-superlattices. Issue 52 (27th May 2016) - Boterashvili, M.; Shirman, T.; Popovitz-Biro, R.; Wen, Q.; Lahav, M.; van der Boom, M. E.
Abstract : We report here how the crystallinity of AuNPs and the choice of binding sites of molecular cross-linkers control their aggregation. Abstract : We report here how the crystallinity of AuNPs and the choice of binding sites of molecular cross-linkers control their aggregation. The combination of different binding moieties ( N -oxides, ArF -I) and the reactivity of the particles' facets allow control over the organization and crystallinity of the AuNP assemblies.